Documentos sobre oficinas de correo "Postmaster" de Mayagüez - Todd, Roberto H.; Medina, P. E.; Salguero Font, Arturo; Domenech, Manuel (My University, 1923)
Documentos sobre oficinas de correo "Postmaster" de Mayaguez
Keywords: Postal service--Puerto Rico.; Servicio postal--Puerto Rico.; New, Harry S.; Marín, Manuel; Pesante, Daniel; Silva, José Ma.; Ramirez de Arellano, Francisco; Partido Republicano (Puerto Rico); Falbe, William; Salguero Font, Arturo; Arrillaga Roqué, Rafael; Tous Soto, José, 1874-1933; Sabater, Carlos; Biaggi, Arturo; Alemar, D. C., Jr.; Castro, Julio P.; Martínez Nadal, Rafael, 1877-1941; Luján, José Jr.; Medina, Pablo E.; Torrens de Arrillaga, Concepción